Examining the Themes of Turkish Children's Literature Through Book Catalogues - Turhan, Osman; Bas, Bayram; Turhan, Fatma Karaca (DERGIPARK AKAD, 2021)
This study sets out to identify themes in Turkish children's literature. Accordingly, Turkish children's literature was examined in terms of child development and education. This study was designed as a case study. Six hundred and sixty-five Turkish children's books were selected from four publishing houses using criterion sampling, and book catalogs were reviewed. Qualitative and quantitative content analysis was administered on the selected children's books according to the Turkish course curriculum themes. Sixteen themes were identified in the children's books. General themes (individual and society, virtues, etc.) were covered in children's books more, while special themes (science and technology, art, etc.) were covered less. When the themes were evaluated in terms of child development, child education, and diversity, some positive and negative results were obtained. Some themes in children's books were not qualified to contribute to child development. Other themes had the potential to support social, mental, emotional, and moral development. However, development areas were not covered in a comprehensive and detailed manner. Children's books had contents suitable for some verbal lessons and verbal competencies in terms of teaching. The same was not true for other courses and competencies. Additionally, children's books had the potential to support children's education on extra-curricular grounds. Finally, a thematically positive and partly limited world was presented in children's books. However, this thematic world displayed may attract the attention of children.
Keywords: Turkish children's literature; book catalogues; theme; child development; child education; Education & Educational Research